New Perspectives on the Use of Phytochemicals as an Emergent Strategy to Control Bacterial Infections Including Biofilms - Anabela Borges (2016)
The majority of current infectious diseases are almost untreatable by conventional antibiotic therapy given the advent of multidrug-resistant bacteria. The degree of severity and the persistence of infections are worsened when microorganisms form biofilms. Therefore, efforts are being applied to develop new drugs not as vulnerable as the current ones to bacterial resistance mechanisms, and also able to target bacteria in biofilms. Natural products, especially those obtained from plants, have proven to be outstanding compounds with unique properties, making them perfect candidates for these much-needed therapeutics. This review presents the current knowledge on the potentialities of plant products as antibiotic adjuvants to restore the therapeutic activity of drugs. Further, the difficulties associated with the use of the existing antibiotics in the treatment of biofilm-related infections are described. To counteract the biofilm resistance problems, innovative strategies are suggested based on literature data. Among the proposed strategies, the use of phytochemicals to inhibit or eradicate biofilms is highlighted. An overview on the use of phytochemicals to interfere with bacterial quorum sensing (QS) signaling pathways and underlying phenotypes is provided. The use of phytochemicals as chelating agents and efflux pump inhibitors is also reviewed.